Building Maintenance Priority Decision Support System Using the Method Profile Matching - Sari, Oryza Lhara; Basyaruddin, Basyaruddin; Khasanah, Uswatun (Universitas Ibn Khaldun Bogor, 2024)
Along with the increasing age of a building, maintenance activities become things that need to be done to minimize damage that occurs such as damage to the ceiling or ceramics. Therefore, this study aims to determine the priority of building elements in the treatment of architectural components in buildings A and B ITK campus using Profile Matching method. Based on the results of analysis and observations in the field, the elements that are the main priority in the architectural component of Building A are ceiling elements, the second priority element is sanitary elements, the third priority element is floor elements and door and window elements, the fourth priority element is painting elements, and the last priority element is Wall pair elements. Whereas in the architectural component of Building B, the main priority elements are ceiling elements and sanitary elements, the second priority element is the wall pair element, the third priority element is the floor element and the door and window element, and the last priority element is the painting element.